Exogenous proline and hormone in combination with compost improves growth and tolerance of maize under heavy metal stress (2020)
Abiotic stress such as heavy metal contamination of agricultural soil limits crop production by disrupting plant’s physiological activities and seed germination. Exogenous proline, hormone and compost have been used to induce growth and stress tolerance in crop but little is known about their interactive and anti-oxidative roles in crop exposed to heavy metal stress. This study assessed the effects of pre-sowing seed soaking with exogenous proline (P) and hormones (Gibberellic acid; GA and Indole-acetic acid; IAA) on the Pb accumulation, osmolytes (P, phenolics; PH and Glycine betaine; GB), Photosynthetic pigments (chlorophyll and carotenoids) and stress indexes (H2O2 and malonialdehyde; MDA) of maize grown on compost amended Pb (23,959 mg kg-1 Pb) contaminated soil. Compost was applied at 20 t ha-1 and 40 t ha-1, P, GA and IAA were applied at 10 mM and 5 mM solely and in combinations to give a total of 34 treatments including control (Distilled water only) and replicated 3 times. Except in IAA treatment, seed pre-treatments with exogenous P and GA and soil amendment with compost generally enhanced chlorophyll production in maize and reduced GB, carotenoids, H2O2 and MDA in treated seeds compared to control. With regards to stress indexes G2+C1 gave the lowest values. Sole application of P1, P2, C2, G1 and I2 enhanced the production of proline in treated plants compared to combined application. Combination with compost was better than hormonal combination. A combination of P2 with C (40 t ha-1) (P2C2) gave the maximum chlorophyll content and reduced the endogenous GB and P. Treatment with P2C2 also reduced Pb accumulation in plant. In conclusion, exogenous application of hormones and proline in combination with organic amendment induces heavy metal tolerance in maize and increased protection against oxidative stress compared to contaminated control. The technique that can enhance crop growth on contaminated soil, reduce metal uptake and provide osmo-protection could be a promising approach.